Romania : 2019 Article IV Consultation-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Romania discusses that growth in 2019 is expected to stay above potential at 4 percent, led by continued fiscal stimulus and strong wage growth, and be accompanied by further widening of current account and fiscal deficits. The focus of discussions was on actions required to curb the widening imbalances and to re-orient the economy toward investment and sustainable income convergence. It is recommended that Romania take advantage of strong growth and start durable fiscal consolidation underpinned by high-quality measures to rein in the twin deficits and improve the macroeconomic policy mix. The more fiscal policy tightens, the less monetary tightening is needed. The report also advises to modernize revenue administration and improve expenditure efficiency. Reassessment of the new pension law to balance social needs and fiscal sustainability is also important. Rising vulnerability calls for a balanced macroeconomic policy mix built on durable fiscal consolidation. High-quality fiscal consolidation would reduce the burden on monetary policy for macroeconomic stabilization, mitigate external pressure by containing the current account deterioration, and bolster growth potential by improving the balance between consumption and investment.